Advances in Parasitic Weed Control at On-Farm Level. Volume I. Joint Action to Control Striga in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
J Kroschel, H Mercer-Quarshie, and J Sauerborn. Margraf Verlag, Germany. 1999. 310 pp.ISBN 3 8236 1302 2.DM45.00 $34.00 Euro 23.00Margraf Verlag,PO Box 1205, D-97985 Eweikersheim, Germany.Fax: + 49 79 348 156Email: margraf@compuserve.com